The effect of anthropogenic disturbance on non-native plant species in Madagascar. (4th October 2016) - Gudiel, A. Andrea; Nieves, Shane C.; Reuter, Kim E.; Sewall, Brent J.
Abstract: Non-native species impact tropical ecosystems, but the role of different anthropogenic disturbances on the success of non-natives remains unclear, especially in island tropical forests. We sought to understand the influence of anthropogenic habitat degradation and disturbance on non-native plant species in Madagascar. Specifically, we evaluated how densities of non-native species of woody shrub ( Lantana camara ), climber ( Mucuna pruriens ) and tree ( Mangifera indica, Albizia lebbeck, Tamarindus indica ) varied with forest habitat degradation and by disturbance type. We surveyed 60400 m 2, recording 482 instances of disturbance and 903 non-native plants in and around the Ankarana National Park. Non-native plant densities were higher in degraded than primary forest. Within degraded forest, densities of non-native trees increased with disturbance. Tree densities correlated with extent of tree damage only in Tamarindus indica, never correlated with extent of tree removal, and always correlated with proximity to roads and trails. Our results suggest roads and trails have relatively greater importance in facilitating the success of non-native tree species than structural changes to habitat. In contrast, densities of Lantana camara and Tamarindus indica did not correlate with any measured type of disturbance; other unmeasured or historical factors may be more important drivers of these smaller, faster-reproducing species.